The Role of the Regions in EU Governance
X, 346 p.
Keywords: This book compares for the first time how the regions in seven different countries (Austria, Belgium, France, Germany, Italy, Spain and the UK) are involved in EU governance. It is also the first book which tackles this matter from two different perspectives; that of EU law and that of comparative law. It includes contributions both from well-established scholars in the field of EU law and from younger scholars.